DOI: 10.35376/10324/46389
|View full text |Cite
|
Sign up to set email alerts
|

Musicoterapia basada en técnicas de música e imagen (MI) como intervención en casos de niños con y sin diagnóstico de Trastorno por Déficit de Atención/Hiperactividad (TDAH): un enfoque mixto

Abstract: Repito y quiero que quede claro: nada de esto habría sido posible sin vosotros. Gracias de corazón.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…The studies reviewed here presented positive results in terms of observed improvements in behavior and attention (Acebes-de Pablo & Carabias-Galindo, 2016;Moutte, 2020); participation, psychomotricity, memory and attention, levels of concentration, and the ability to communicate with specialists, teachers, and peers (Blasco Magraner & Valero, 2017;Fong & Jelas, 2010;Garrote Rojas et al, 2018;McFerran et al, 2016;Schmid et al, 2020); and levels of aggression (Epelde-Larrañaga et al, 2020). The benefits observed seemed to be most significant when interventions were of long duration, as in the case of Mendelson et al (2016).…”
Section: Main Descriptorsmentioning
confidence: 72%
See 1 more Smart Citation
“…The studies reviewed here presented positive results in terms of observed improvements in behavior and attention (Acebes-de Pablo & Carabias-Galindo, 2016;Moutte, 2020); participation, psychomotricity, memory and attention, levels of concentration, and the ability to communicate with specialists, teachers, and peers (Blasco Magraner & Valero, 2017;Fong & Jelas, 2010;Garrote Rojas et al, 2018;McFerran et al, 2016;Schmid et al, 2020); and levels of aggression (Epelde-Larrañaga et al, 2020). The benefits observed seemed to be most significant when interventions were of long duration, as in the case of Mendelson et al (2016).…”
Section: Main Descriptorsmentioning
confidence: 72%
“…The studies reviewed reached a range of interesting conclusions, including that music therapy is a vehicle for expression that enables communication (Arnau, 2013); that it is a valid intervention in the case of SEN students (Fong & Jelas, 2010;Talavera Jara & Gértrudix Barrio, 2016) and mainstream students (Chao-Fernández et al, 2020;Crooke & McFerran, 2014;Gee et al, 2019); and that there are many benefits from interdisciplinary collaboration (Ballantyne & Baker, 2013), with music education providing the ideal curricular space for such interactions (Acebes-de Pablo & Carabias-Galindo, 2016;Brown et al, 2018;Smith, 2018). Studies also confirmed the efficacy of music therapy in improving behavior, socializing, and integrating students, so contributing to their well-being and overall development (Blasco Magraner & Valero, 2017;Días Teixeira & Silva Fernandes, 2021;McFerran et al, 2016;Schmid et al, 2020).…”
Section: Main Descriptorsmentioning
confidence: 99%
“…(Llanga e Insuasti, 2019), Los niveles de intensidad de la música en el ambiente pueden interpretarse como una invitación directa al trabajo, a la atención y a aprender algo nuevo; para ello se enunciaron cada una de las técnicas de intervención incluidas dentro de la musicoterapia activa, como la improvisación, la composición y la recreación. (Acebes, 2020).…”
Section: Zonas Cerebrales Estimuladas Por La Músicaunclassified